Computer Assisted Learning: Assessment of the Veterinary Virtual Anatomy Education Software IVALA™ - Little, William Brady; Artemiou, Elpida; Conan, Anne; Sparks, Cathryn (My University, 2018)
Although cadaveric dissection has historically been the cornerstone of anatomical education, it comes at the cost of some emotional, moral, safety, and environmental concerns. Computer assisted learning (CAL) programs are an increasingly common solution to these issues; however, research regarding the efficacy of high fidelity simulation is limited. The traditional first semester veterinary gross anatomy course curriculum at Ross University School of Veterinary Medicine (RUSVM) was supplemented with a web based virtual anatomy program, IVALA™ (www.ivalalearn.com). The purpose of this study was to assess the relationship between supplementary use of the IVALA™ program and student examination scores, and to measure student perception surrounding IVALA™. IVALA™ uses an interactive virtual canine specimen that enables students to identify, move, rotate, magnify, and remove individual anatomic structures while providing a text description of each selected anatomic point. Fifty-six first semester RUSVM students who supplemented their anatomic learning with the IVALA™ program performed significantly higher on examinations compared to students (n = 123) that did not (p = 0.003). Students’ overall perception toward IVALA™ was enjoyable (mean = 3.8 out of a 5-point Likert scale) and beneficial to their knowledge of anatomy (mean = 3.7); however, students did not support replacing cadaveric dissection with CAL (mean = 2.1). CAL can effectively supplement learning outcomes for veterinary anatomy.
Citation: Little, W.B.; Artemiou, E.; Conan, A.; Sparks, C. Computer Assisted Learning: Assessment of the Veterinary Virtual Anatomy Education Software IVALA™. Vet. Sci. 2018, 5, 58.
Keywords: Blended Learning; Computer Assisted Learning (Cal); Educational Methods; Gross Anatomy; Veterinary Anatomy Education; Virtual Anatomy